Utilization of Immobilized Green Algae Scenedesmus qudricauda as A Sustainable Method to Remove Some Industrial Textile Dyes - Zahraa Hussein Obaid; Jasim M. Salman; Shaimaa Satae M. Ali; Esraa Abdul-Adel; Sarab A. Juda (مجلة ديالى للعلوم الزراعية)
The textile industry is a growing global sector that creates many jobs and boosts the country's economy. However, it is a major source of water pollution that threatens aquatic life and human health. Therefore, it has become necessary to find new methods that are effective, sustainable, and low-cost to remove these dyes from wastewater. The research aims to investigate the capacity of Scenedesmus quadricauda algae to adsorb textile dyes Reactive Yellow 145, and Disperse Yellow 114 from aquatic media by studying the effects of 5 variables on the dye removal efficiency, including initial dye concentration (10-50 ppm), contact time (3-12 days), pH (5-9), temperature (4-40 C°), and adsorbent dosage (0.1-2.5 g L-1) The current study's results revealed that the immobilized algae achieved the highest color removal percentages of 98% and 97% for the dyes Reactive Yellow 145 and Disperse Yellow 114, respectively. Most decolorization activity was found at an initial concentration of 40 mg L-1, 9 days of contact, a pH value of 5, a temperature of 25°c, an algae dosage of 2.5 g L-1, and a stirring speed of 120 rpm. The spectrophotometer method was used to verify this. In addition, SEM and FTIR analysis of the immobilized biomass of S. quadricauda were performed before and after dye treatment. It was found that the immobilized algae biomass had high biosorption properties associated with its surface structure and active groups, proving the immobilization effectiveness.